NAEGLERIA FOWLERI: RISING CASES DUE TO A UNIQUE STRAIN IN PAKISTAN - Syed Shabbir Afzal; Aabiya Arif; Priyanka Mohan Lal (Journal of Ayub Medical College Abbottabad, 2021)
Naegleria Fowleri is a pathogenic flagellate amoeba that can cause primary amoebic meningoencephalitis, a potentially fatal brain infection (PAM). PAM symptoms are similar to those of bacterial and viral meningitis, including fever, headache, stiff neck, nausea, vomiting, anorexia, and, in rare cases, seizures. Although this amoeba cannot live in saline water, the majority of cases recorded indicate that it thrives in saline residential water supplies, which is both surprising and concerning. In 2021 alone, Pakistan recorded six deaths due to naegleria fowleri in a span of just two-month, five from Karachi and one from Balochistan. The number of deaths caused by naegleria fowleri is steadily rising in Pakistan, moreover, There is currently no treatment for Naegleria, which is extremely concerning given that it has a death rate of 95-99 percent. As a result, preventative measures such as chlorinating water tanks, performing correct diagnostic tests, and utilizing distilled water for ablution procedures, among other things, play an important part in combating this disease.